2019
DOI: 10.3390/ani9060306
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Echotextural Attributes of Pectoralis Major Muscles in Broiler Chickens: Physicochemical Correlates and Effects of Dietary Fat Source

Abstract: This study examined the relationships among physicochemical properties and ultrasonographic image attributes of pectoralis major muscles in broiler chickens. Forty male Ross 308 chicks were randomly assigned to four equinumerous fat-supplementation groups (Group SO: soybean oil; Group FO: flax oil; Group SO + FO: soybean oil + flax oil; and Group BF: beef fat). Ultrasonograms of birds’ pectoral muscles were obtained just before slaughter at 6 weeks of age and were subjected to digital image analyses to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 19 publications
0
16
3
1
Order By: Relevance
“…In spite of tremendous variations in muscle size within (e.g., slow-twitch vs. fast-twitch vs. hybrid fibers) and between different skeletal muscles (Smith and Fletcher 1988), the average diameter of human muscle fibers is 1.5-to 2-fold greater compared with that of chickens' (Koomkrong et al, 2015;Meznaic and Cvetko, 2016). This relatively small size may explain a lack of inter-plane differences in muscle echotexture in the present study as well as a lack of correlations between quantitative echotextural attributes and pectoral muscle fiber diameters in a recent study in broiler chickens (Schwarz et al, 2019). Therefore, it is logical to infer that differences in echotextural attributes between the four groups of broiler chickens were predominantly due to the chemical composition of the muscle.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In spite of tremendous variations in muscle size within (e.g., slow-twitch vs. fast-twitch vs. hybrid fibers) and between different skeletal muscles (Smith and Fletcher 1988), the average diameter of human muscle fibers is 1.5-to 2-fold greater compared with that of chickens' (Koomkrong et al, 2015;Meznaic and Cvetko, 2016). This relatively small size may explain a lack of inter-plane differences in muscle echotexture in the present study as well as a lack of correlations between quantitative echotextural attributes and pectoral muscle fiber diameters in a recent study in broiler chickens (Schwarz et al, 2019). Therefore, it is logical to infer that differences in echotextural attributes between the four groups of broiler chickens were predominantly due to the chemical composition of the muscle.…”
Section: Discussioncontrasting
confidence: 61%
“…Examples of the first order descriptors include the mean, standard deviation, variance, skewness, and kurtosis of numerical pixel values (Haralick, 1979;Molinari et al, 2015). It was shown that intramuscular fat content of the longissimus dorsi muscle in lambs and cattle (Slósarz et al, 2001;Newlacil et al, 2013) and certain physicochemical properties of pectoral muscles in broiler chickens (Schwarz et al, 2019) could be determined using ultrasonographic imaging combined with computer-assisted analyses of first order echotextural variables.…”
mentioning
confidence: 99%
“…There is a great deal of evidence that ultrasound imaging combined with computerized image analysis can be used to predict histochemical characteristics of various internal organs and tissues. Some experimental and clinical studies have reported a link between echogenicity and tissue physicochemical properties (e.g., human dystrophic muscles [26], ram testes [3] and chicken pectoralis major muscle [7]). In 1998, Amin et al [27] showed that image-processing analysis could be used to predict intramuscular fat content from ultrasound images obtained in live beef cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Both echotextural variables are objective measures of tissue echogenic properties and valuable indicators of corresponding histophysiological changes. In fact, the echotextural attributes of the tissue are the function of its cellular density, hydration, compressibility, macromolecular content and general chemical composition [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Protein and lipid content of the tissue may determine its ultrasonographic appearance (Ahmadi et al, 2013). Significant correlations exist between ultrasonographic image characteristics and chemical composition of the testes (Ahmadi et al, 2013) and skeletal muscles (Clague et al, 1995;Schwarz et al, 2019). Mean PSD values of testicular tissue in the ram were positively correlated with extractable lipids (Ahmadi et al, 2013).…”
Section: Scanning Order/breedmentioning
confidence: 99%